INFLUENCE OF ORIGIN AND SIZE OF POTATO PLANTING MATERIAL ON MORPHOLOGICAL CHARACTERISTICS OF SEED TUBERS - Poštić, Dobrivoj; Štrbanović, Ratibor; Broćić, Zoran; Popović, Tatjana; Marković, Sanja; Jelušić, Aleksandra; Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2021)
The aim of this study was to determine the influence of the origin and size of planting material on the mophological characteristics of seed tubers three potato cultivars. The objects of research were three varieties of potatoes: two middle early (Aladdin and Newton) and middle late (Desiree). The analysis of the morphological characteristics tuber showed highly significant (р<0.01) differences under influenced origin planting material (factor O) and size of seed tuber (factor S). Significance influence (р<0.01) genotype (factor G) was detected on number of sprouts per tuber and sprouts length. Seed tubers originating from a lower altitude (350 m a.s.l.) formed a significantly (р<0.01) greater number of sprout per tuber, 0.59 or 7.33% more in comparison with the number sprouts per tuber originating from of 1300 m a.s.l. Statistical analysis of the number of sprouts per tuber showed a significantly (р<0.01) lower number of germs in fractions of 40 and 60 g, compared to the larger fraction of 80 g. Larger number of sprouts per seed tuber (at a lower altitude) results in the formation of a greater number of primary stems per potato plant, i.e. production of more number of tubers of medium size under regular and favorable conditions (seed production). Larger diameter of sprout and longer sprout length per tuber (at higher altitudes) will form a smaller number of primary stems per plant should be used in shorter seasonal production (early potatoes) and marketable production when a smaller number of large tubers were needed.